Alcohol‐related biases in selective attention and action tendency make distinct contributions to dysregulated drinking behaviour. (5th July 2013) - Sharbanee, Jason M.; Stritzke, Werner G. K.; Wiers, Reinout W.; MacLeod, Colin
Abstract: Aims: To assess whether alcohol‐related biases in selective‐attention and action tendency uniquely or concurrently predict the ability to regulate alcohol consumption. Design and participants: Two groups of undergraduate social drinkers (total n  = 55) who differed in their ability to regulate their alcohol consumption completed a novel Selective‐Attention/Action‐Tendency Task (SA/ATT), which assessed separately alcohol‐related biases in selective attention and action tendency. Setting: University of Western Australia, Australia. Measurement: Dysregulated drinking was operationalized as a self‐reported high level of alcohol consumption on the Alcohol Consumption Questionnaire, and a high desire to reduce consumption on the Brief Readiness to Change Algorithm. Selective attention and action tendency were assessed using the SA/ATT, working memory was assessed using the operation‐span task and participant characteristics were assessed using the Alcohol Use Disorders Identification Test (AUDIT) and Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). Findings: Results indicated that (i) there was no significant association between alcohol‐related biases in selective attention and action tendency, r  = 0.16, P  = 0.274, and (ii) biases towards alcohol, in both selective attention, β = 1.01, odds ratio = 2.74, P  = 0.022, and action tendency, β = 1.24, odds ratio = 3.45, P  = 0.015, predicted independent variance in dysregulated‐drinker status. Conclusion: Biases in selective attention and action tendency appear to be distinct mechanisms that contribute independently to difficulty regulating alcohol consumption. Treatment components that could be combined to target both mechanisms could enhance treatment outcomes for alcohol‐use disorders.